(untitled) (Journal of Laboratory Animal Science, 2024)
Immunophenotyping by flow cytometry is one of the most rapid way of doing analysis & identification of heterogeneous populations of cells by using cell-specific fluorochrome-conjugated antibodies as probes. Immunophenotyping of laboratory animals is essential to monitor the immune status of the laboratory animals for better maintenance and management of animal facilities for immunological studies. The spleen is one of the major organs in immunity and plays a key role in the production and maintenance of red blood cells and the production of certain circulating white blood cells. Therefore, we harvested the spleen from various mice strain (Swiss Albino, BALB/C, C57BL, and C3HeJ) available at Central Animal Facility of Indian Institute of Science and did quantification of various types of immune cells by multicolor flow cytometry. 1X107 splenocytes were taken in the eppendorf tubes and labeled with T cell, B cell, CD4+ and CD8+ cells specific antibodies and 30,000 events were acquired in the BD FACS Canto™ II (BD Biosciences) and the results were analyzed by FACS Diva software version 6.1.1. It was found that C57BL has higher percentage of B Cells (60±10%) followed by C3HeJ (49±2%). BALB/C has higher number of T cells (54±4%) followed by Swiss Albino strain (46±4%). BALB/C has higher percentage of CD4+ Cells (39±3%) as compared to other strains. In most of the strains the B Cells population is more followed by T Cells, CD4+ Cells & CD8+ Cells. Moreover, splenocytes percent profile of Scid and Nude mice were taken as standard.